Critical Reflection on My PhD Research Experience - Ibrahim, Habibie Bte Hj; Johnson, Sally; Gilligan, Philip; Adu-Gyamfi, Jones (International Journal of Asian Social Science, 2018)
This article offers a selective account of the author's personal experience with the critical self-reflective inquiry. This article also described the selection of research participants, the researcher's position, trustworthiness, the issue of informed consent, and how confidentiality was maintained throughout the present research study.